Microbiological and sensory analysis of tilapia (Oreochromis niloticus) fillets with bioactive coating incorporating oregano (Origanum vulgare) essential oil - Aguilar Paquirachín, Esmeralda (2024)
Fish products are rich sources of nutrients; however, they are highly susceptible to alteration and spoilage. This study evaluated the microbiological, sensory and pH effects of a bioactive coating incorporating oregano essential oil (0, 2, 3 and 4 %) on refrigerated tilapia fillets at 4°C for 1, 4, 7 and 11 days. A 4Ax4B factorial design was used, A: concentration of essential oil and B: storage time in days, with three replicates. Friedman and Kruskal-Wallis tests were used. The fillets treated with coating and essential oil showed absence/25 g of Salmonella sp., with levels of mesophilic aerobes (2x105CFU/g), total psychrophilic aerobes (7x103 CFU/g), total facultative psychrophilic anaerobes (3.18x104 CFU/g), Escherichia coli (8 CFU/g) and Staphylococcus aureus (4×102 CFU/g); all within the limits established by Technical Standard No. 071-MINSA/DIGESA. The coated fillets showed superior sensory characteristics compared to untreated fillets, maintaining a pH between 6.28-6.4, up to day seven with 4% essential oil. It is concluded that these results and their application constitute a promising alternative for the primary processing industry of this species.